2004
DOI: 10.1139/w04-009
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen transfer and assimilation between the arbuscular mycorrhizal fungus Glomus intraradices Schenck & Smith and Ri T-DNA roots of Daucus carota L. in an in vitro compartmented system

Abstract: Nitrogen metabolism was examined in monoxenic cultures of carrot roots (Daucus carota L.) colonized with the arbuscular mycorrhizal (AM) fungus Glomus intraradices Schenck & Smith. Glutamine synthetase and glutamate dehydrogenase activities were significantly increased in mycorrhizal roots for which only the extraradical mycelium had exclusive access to NH4NO3 in a distinct hyphal compartment inaccessible to the roots. This was in comparison with the water controls but was similar to the enzyme activities of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(67 citation statements)
references
References 48 publications
(62 reference statements)
3
61
1
2
Order By: Relevance
“…However, there are numerous reports in which a significant transport of N by AM fungi to their host has been demonstrated. In AM root organ cultures, 21% of the total N in the roots were taken up by the ERM [102]; and in similar experiments even higher proportions were observed [103]. In maize, 75% of the N in the leaves were taken up by the ERM of an AM fungus [104].…”
Section: Uptake Of Nitrogen From the Soilmentioning
confidence: 66%
See 1 more Smart Citation
“…However, there are numerous reports in which a significant transport of N by AM fungi to their host has been demonstrated. In AM root organ cultures, 21% of the total N in the roots were taken up by the ERM [102]; and in similar experiments even higher proportions were observed [103]. In maize, 75% of the N in the leaves were taken up by the ERM of an AM fungus [104].…”
Section: Uptake Of Nitrogen From the Soilmentioning
confidence: 66%
“…NH4 + has often been described as the preferred N source of mycorrhizal fungi, because its uptake is energetically more efficient than the uptake of NO3 - [13,102,105]. However, ECM fungi differ in their ability to absorb NO3 -from the soil, and some ECM fungi have been shown to produce a greater biomass when supplied with NO3 -compared to NH4 + [107].…”
Section: Uptake Of Nitrogen From the Soilmentioning
confidence: 99%
“…Tyrosine and phenylalanine are important precursors of some secondary metabolites, such as rosmarinic and caffeic acids (Petersen and Simmonds 2003). Consequently, AM symbiosis can enhance the synthesis of certain amino acids and contribute to the accumulation of specific metabolites by promoting N uptake (Smith and Read 1997;Toussaint et al 2004). Some research has also shown that symbiosis with AM fungi results in the increase of terpenoids and phenolic acids, which may result from increased absorption of mineral nutrients, especially P and N (Kapoor et al 2002a, b;Toussaint et al 2007).…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Assimilation of NH + 4 is a principal means of N absorption in AM fungal systems (Hawkins et al, 2000;Toussaint et al, 2004). N uptake and incorporation into amino acids via the glutamine synthetase/glutamate synthase (GS/GOGAT) cycle has been found in AM fungi (Smith et al, 1985).…”
Section: Nitrogen Transfer At the Mycorrhizal Interfacementioning
confidence: 99%